Daylight Saving Time and Its Effect on Asset Valuation: Evidence for Chile, Brazil and Mexico - González, Marcelo; Contreras, Silvana; Rodríguez, Arturo (Estudios de Administración, 2011)
The literature on behavioral finance suggests that research findingson the psychology area might be helpful to understand several features of financial markets. Our study fits into this current. Wedraw on sleep research and address the question if sleep disruptionhas any effects on the stock market. We use daylight-saving timechanges as a proxy for sleep disruptions. Our sample includes three Latin American markets: Chile, Brazil and Mexico. We find that,after controlling for the weekend (or Monday) effect, there is nosignificant relation between stock returns and daylight-savings timechanges in our sample.